Clinical evidence of growth hormone for infertile women with diminished ovarian reserve undergoing IVF: a systematic review and meta-analysis - Lin, Guangyao; Zhong, Xiufang; Li, Shengnan; Xu, Lianwei (Frontiers in Endocrinology, 2023)
Objective: To appraise the current randomized clinical trials (RCTs) for evidence of the association of growth hormone (GH) with improved outcomes in infertile women with diminished ovarian reserve (DOR) undergoing in vitro fertilization (IVF).Methods: Relevant RCTs published in Chinese or English were identified through a comprehensive search of nine databases from the period of database inception to April 20, 2023. We included trials investigating adjuvant GH during ovarian stimulation and reported the subsequent outcomes. The group with adjuvant GH treatment and the group without adjuvant GH treatment were set up as the trial and control groups, respectively. The quality of RCTs was measured according to the Cochrane Collaboration Handbook.Of the 579 studies initially identified, 10 RCTs comprising 852 infertile women with DOR were included. The GH dose of individual trials ranged between 3 with GH during ovarian stimulation protocols showed better clinical outcomes, shorter days and lower dosages of gonadotrophin required. Furthermore, well-designed RCTs are needed to verify our results in the future.